A new butterfly species from south Russia revealed through chromosomal and molecular analysis of the Polyommatus (Agrodiaetus) damonides complex (Lepidoptera, Lycaenidae) - Lukhtanov, Vladimir A. (Comp Cytogenet, 2017)
Abstract. Finding a new species is a rare event in easy-to-see and well-studied organisms like butterflies, especially if they inhabit well-explored areas such as the Western Palaearctic. However, even in this region, gaps in taxonomic knowledge still exist and here we report such a discovery. Using a combined analysis of chromosomal and molecular markers we demonstrate that Polyommatus blue populations from Daghestan (South Russia), previously identified as P. aserbeidschanus, represent in fact a new species which is described here as P. australorossicus sp. n. We also show that the enigmatic Polyommatus damonides described as a form of Polyommatus damone and later considered as an entity similar to P. poseidon or P. ninae is conspecific with a taxon previously known as P. elbursicus. As a result of our study, we propose several taxonomic changes within the P. damonides species complex and suggest the following new combinations: P. damonides elbursicus Forster, 1956, comb. n. and P. damonides gilanensis Eckweiler, 2002, comb. n.